2022
DOI: 10.3390/ijerph19159601
|View full text |Cite
|
Sign up to set email alerts
|

What Builds Resilience? Sociodemographic and Social Correlates in the Population-Based LIFE-Adult-Study

Abstract: Resilience is closely related to mental health and well-being. Identifying risk groups with lower resilience and the variables associated with resilience informs preventive approaches. Previous research on resilience patterns in the general population is heterogeneous, and comprehensive large-scale studies are needed. The aim of our study is to examine sociodemographic and social correlates of resilience in a large population-based sample. We examined 4795 participants from the LIFE-Adult-Study. Assessments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
3
8
1
1
Order By: Relevance
“…In this study, married people had higher resilience than single people. This result is in line with results of some others studies [30,32,35], and may be because married people have better support networks than single people. On the other hand, researchers show that people with higher education had higher resilience scores [29,30,35,36], the results of this confirmed this finding, too.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, married people had higher resilience than single people. This result is in line with results of some others studies [30,32,35], and may be because married people have better support networks than single people. On the other hand, researchers show that people with higher education had higher resilience scores [29,30,35,36], the results of this confirmed this finding, too.…”
Section: Discussionsupporting
confidence: 92%
“…In term of the relationship between gender and resilience, researchers reported different results. Some studies reported higher levels of resilience score in women [29,30] and others found higher resilience in men [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, another interesting question for future studies is whether the link between resilience and mental health is the same for all groups or whether it is moderated by other factors. Previous studies suggest that resilience tends to be stable across age [ 13 , 14 , 15 ], whereas younger participants were more burdened by mental health symptoms in our study. This could point out a lower relevance of resilience at younger age, which should be investigated in future studies.…”
Section: Discussioncontrasting
confidence: 41%
“…High resilience among the elderly was discussed as an underlying factor for relatively stable well-being in the old age population [ 10 , 11 , 12 ]. Previous studies indicate that resilience tends to be stable or increases over the life course, which could be attributed to life experience and crises successfully overcome [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation